Predação de ovócitos de Piaractus mesopotamicus (pacu-caranha) por Macrobrachium amazonicum em condições laboratoriais - Silva, Thiago Elias da [UNESP]; Taddei, Fabiano Gazzi (Inst Pesca, 2014)
The preference of predation on oocytes of Piaractus mesopotamicus, commonly known as 'Pacucaranha', by the prawn Macrobrachium amazonicum, under laboratory conditions, was evaluated regarding to other food items. The prawns were collected with sieves, placed below the underwater vegetation, and maintained in aquarium (12 L each) at a density of 10 individuals/aquarium for acclimatization. Oocytes (O) of P. mesopotamicus were obtained from the disposal of artisanal fishery. Artificial feed (R), fish muscle (M), organic matter accumulated in roots of Salvinia sp. (S) and plant organic matter in decomposition (MV) items were used to compare the preference by M. amazonicum. In all experiments the average of the prawns preying oocytes were higher; significant differences were detected only when comparing O/P and O/M. The preference for oocytes may be due to the presence of yolk, which has a high nutritional value and easy assimilation, in contrast to others items, which resent certain rigidity. This prawn species is exotic on site and the results of this study shows a possible environmental impact on P. mesopotamicus in the region.
Oocytes' predation of piaractus mesopotamicus (pacu-caranha) by macrobrachium amazonicum, under laboratory conditions
Keywords: Characidae; Crustacea; Palaemonidae; predation; trophic relationship